Adopting Halal Logistics for Sustainable Food Security in Disaster Management - Rohafiz Sabar; Nur Khairiel Anuar; Mohamad Sidik Awang Adi (Penerbit USIM, 2025)
International Halal Management Conference (IHMC) : “Empowering Halal Industry Towards Globalization” / Editor :-Farah Laili Muda @ Ismail, Nur Ainna Ramli & Anita Ismail Organized by Faculty of Economics & Muamalat, Universiti Sains Islam Malaysia 9 September 2025